Analysis of the Influence of Financial Technology, Internal Performance, Macroeconomic Factors on Profitability of Islamic Banks In Indonesia - Nurjanah, Nunung; Amrizal, Amrizal (ITB AAS INDONESIA Surakarta, 2024)
This study aims to analyze the profitability of Islamic Banks in Indonesia by considering internal performance factors, macroeconomic factors, and the influence of financial technology. Profitability is a crucial indicator in evaluating the financial performance of banks and maintaining their operational viability in a competitive market. This study uses a quantitative approach with secondary data from the financial statements of 10 Islamic Banks in Indonesia over a certain period (10 years). Internal performance variables that are the focus of the study include traditional profitability ratios such as Return of Assets (ROA) and Return on Equity (ROE), as well as factors such as NPF (Non-Performing Financing). In addition, macroeconomic factors such as interest rates, national economic growth, and inflation, are also considered in this analysis. The results showed that partially the variables FDR (X1), INFLATION (X5), INTEREST (X6), INTEREST RATE (X7), GDP (X8), FINTECH (X9) had no effect on ROA (Y). However, the variables BOPO (X2), DPK (X3) and SIZE (X4) have an effect on ROA (Y), where the value obtained based on the probability is 0.0000 (X2), 0.0153 (X3) and 0.0548 (X4). However, when viewed simultaneously, the Independent variables jointly affect the dependent variable.